Sodium-ion battery positive electrode active material Na4Fe (PO4) 2P2O7 as well as preparation method and application thereof

By using Na4Fe(PO4)2P2O7 as the positive electrode active material of sodium ion battery, using hydrothermal reaction method and citric acid as a multifunctional precursor, the problem of capacity loss and insufficient cycle life of existing sodium ion battery positive electrode materials is solved. , achieving high specific capacity and stable cycle performance.

CN119447284APending Publication Date: 2025-02-14SUZHOU PUNA NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310959777.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode active materials have problems such as capacity loss, short cycle life, and unfast reaction rate, which is difficult to meet the high performance and stability needs of sodium ion batteries.

Method used

Na4Fe(PO4)2P2O7 is used as the positive electrode active material of sodium ion battery, and the material is prepared by hydrothermal reaction method, and citric acid is used as a multifunctional precursor, which has both the role of a chelating agent, a reducing agent and a carbon source during the synthesis process.

Benefits of technology

Na4Fe(PO4)2P2O7 material exhibits high specific capacity and stable circulation performance, and maintains good cycle stability under high temperature environment of 60℃, solving the problem of capacity loss and short cycle life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode active material Na4Fe (PO4) 2P2O7 as well as a preparation method and application thereof, and relates to the technical field of secondary battery positive electrode materials. According to the invention, a hydrothermal reaction step is adopted, and a target product is prepared by mixing raw materials in a stoichiometric ratio and reacting under specific conditions. In the method, citric acid or citrate is used as a multifunctional precursor, and has the effects of a chelating agent, a reducing agent and a carbon source in the synthesis process. The invention provides a simple and effective method for preparing the Na4Fe (PO4) 2P2O7 positive electrode active material, which can be used in the field of sodium ion batteries and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery positive electrode materials, and in particular to a sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 and a preparation method and application thereof. Background Art

[0002] As an important component of sodium-ion batteries, the positive electrode of sodium-ion batteries has requirements for energy storage, energy release and stable circulation. Traditional lithium-ion batteries have been widely used, but their material costs are high and lithium resources are relatively scarce. Therefore, it has become increasingly important to research and develop a sodium-ion battery with lower costs and more abundant resources.

[0003] At present, many different types of positive active materials for sodium-ion batteries have been developed, including oxide materials, sulfur compound materials, organic materials, etc. Among them, oxide materials are one of the most common positive active materials for sodium-ion batteries. Early nanostructured ferrite is a positive active material for sodium-ion batteries with good sodium ion embedding performance and high capacity. With the deepening of research, other transition metal oxides such as lithium nickel oxide, sodium vanadate, sodium cobalt oxide, sodium manganate, and manganese-cobalt composite oxides have gradually become research hotspots. In addition, phosphates, sulfates, sulfides, and organic materials are also gradually receiving attention in the research of positive active materials for sodium-ion batteries.

[0004] However, existing positive electrode active materials for sodium ion batteries still have certain problems, such as capacity loss, short cycle life, slow reaction rate, etc. Therefore, research and development of positive electrode active materials for sodium ion batteries with higher performance and stability is of great significance for the commercial application of sodium ion batteries.

[0005] Layered metal oxides have been extensively studied and applied in sodium-ion laboratories. The main issues that need to be addressed are material cost, structural stability, and improvement of energy density. Prussian blue analogs show impressive energy density at a very low cost due to the use of cheap elements such as iron, manganese, carbon, and nitrogen. However, the structure is easily destroyed by water molecules in the ambient atmosphere, which makes industrial processing very difficult. In addition, there are concerns that cyanide may be released from the material when heated, which is extremely dangerous in the event of a crash or fire accident. In terms of cost, nickel-rich layered cathode materials are excluded because the price of nickel is very high, despite the high capacity. In terms of performance, Ti-rich layered materials cannot operate in the acceptable voltage range for cathode materials and are therefore eliminated. In terms of cycle life, Fe-rich layered materials have a relatively short cycle life due to their low relative humidity compared to Fe. 4+ Parasitic reactions and Fe 4+Migration to the sodium layer is subject to severe electrolyte oxidative decomposition, which is a poor choice. The only candidate material with the potential to meet these requirements is layered manganese-rich materials.

[0006] In fact, the development of manganese-rich lithium cathode materials did not flourish in the end, mainly due to: 1) the aggressive demand for high capacity; 2) Mn dissolution at high operating voltage; 3) Mn migration to the lithium layer; 4) Mn 3+ Structural deformation caused by the Jahn-Teller effect; 5) oxygen release.

[0007] Based on the above reasons, this application is filed. Summary of the invention

[0008] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 (abbreviated as: NFPP) and its preparation method and application, to solve or at least partially solve the above technical defects existing in the prior art: the co-substitution of transition metals Fe and P and the sodium-rich structure are the main factors for improving the specific capacity and cycle stability, paving the way for the application of sodium-rich iron oxyphosphate in the positive electrode of sodium ion batteries.

[0009] In order to achieve the above first object of the present invention, the technical solution adopted by the present invention is as follows:

[0010] A sodium ion battery positive electrode active material, whose chemical formula is Na4Fe(PO4)2P2O7.

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7, the method specifically comprising the following steps:

[0012] (1) Reaction step: dissolving a sodium source, a phosphorus source, an iron source, citric acid or a citrate in a suitable amount of a dispersant in a stoichiometric ratio to form a reaction mixture; and then reacting the reaction mixture at 60-80° C. for 5-10 hours;

[0013] (2) Post-treatment step: pour the solution obtained in step (1) into an autoclave, continue heat treatment at 100-500° C. in an inert atmosphere for 2-48 hours, and then cool to room temperature; then ultrasonically treat the obtained solution to increase dispersibility; finally, evaporate the water in the solution by heating to obtain a powdered product, namely the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7.

[0014] Further, in the above technical scheme, the sodium source in step (1) is any one of sodium acetate, sodium hydroxide, sodium carbonate, sodium oxalate, sodium nitrite, disodium hydrogen phosphate, sodium bicarbonate, sodium citrate, anhydrous sodium sulfate, sodium stearate, sodium oleate, sodium tartrate, sodium alginate, sodium carboxymethyl cellulose, sodium lactate or sodium humate, or a combination of at least two thereof: for example, it can be any one of sodium acetate, sodium hydroxide, sodium carbonate, sodium oxalate, sodium nitrite, disodium hydrogen phosphate, sodium bicarbonate, sodium citrate, anhydrous sodium sulfate, sodium stearate, sodium oleate, sodium tartrate, sodium alginate, sodium carboxymethyl cellulose, sodium lactate or sodium humate. Typical but non-limiting combinations are: sodium acetate and sodium hydroxide, sodium carbonate and sodium oxalate, sodium nitrite and disodium hydrogen phosphate, sodium bicarbonate and sodium citrate, sodium stearate and sodium oleate, sodium tartrate and sodium alginate, sodium carboxymethyl cellulose, sodium lactate and sodium humate, etc.

[0015] Further, in the above technical scheme, the phosphorus source in step (1) is any one of white phosphorus, yellow phosphorus, black scale, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphine, phosphorus trioxide, phosphorus pentoxide, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphoric acid, or a combination of at least two of them: for example, it can be any one of white phosphorus, yellow phosphorus, black scale, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphine, phosphorus trioxide, and phosphorus pentoxide. Typical but non-limiting combinations are: white phosphorus and yellow phosphorus, black scale and white phosphorus, phosphoric acid and phosphorous acid, hypophosphorous acid and phosphoric acid, phosphorus trioxide and phosphorus pentoxide, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid, diammonium dihydrogen phosphate and phosphoric acid, etc.

[0016] Furthermore, in the above technical solution, the iron source in step (1) is at least one of ferrous sulfate, ferric sulfate, ferric nitrate and ferric acetate.

[0017] Furthermore, in the above technical solution, the citrate in step (1) is sodium dihydrogen citrate (sodium hydrogen citrate) and / or trisodium citrate (trihydrate). The citric acid or citrate is a multifunctional precursor that acts as a chelating agent, a reducing agent, and a carbon source during the synthesis process.

[0018] Furthermore, in the above technical scheme, the dispersant in step (1) is any one of deionized water, ethanol or ethylene glycol, or a combination of at least two of them. For example, it can be any one of deionized water, ethanol or ethylene glycol. Typical but non-limiting combinations are: deionized water and ethanol, deionized water and ethylene glycol, ethanol and ethylene glycol, deionized water, ethanol and ethylene glycol.

[0019] Furthermore, in the above technical solution, the inert gas used in the inert atmosphere in step (2) is any one of nitrogen, argon or helium, or a combination of at least two of them. For example, it can be any one of nitrogen, argon or helium. Typical but non-limiting combinations are: nitrogen and argon, nitrogen and helium, argon and helium, nitrogen, xenon and helium.

[0020] Furthermore, in the above technical scheme, the temperature of the heat treatment in step (2) is 100-500°C, for example, it can be 100°C, 200°C, 250°C, 300°C, 350°C, 400°C or 500°C, as well as specific point values ​​between the above numerical values. Due to limited space and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0021] Furthermore, in the above technical scheme, the time of the heat treatment in step (2) is 2-48h, for example, it can be 2h, 5h, 7h, 8h, 9h, 10h, 11h, 20h, 30h or 48h, as well as specific point values ​​between the above numerical values, are not exhaustively listed in the present invention due to space limitations and for the sake of simplicity.

[0022] Furthermore, the above technical solution, if necessary, further comprises step (3): sintering the powdered product obtained in step (2) under a protective atmosphere to improve the density and stability of the product.

[0023] Furthermore, in the above technical solution, the sintering treatment in step (3) is carried out in a protective atmosphere, and the protective atmosphere is any one of nitrogen, argon or helium, or a combination of at least two of them. For example, it can be any one of nitrogen, argon or helium. Typical but non-limiting combinations are: nitrogen and argon, nitrogen and helium, argon and helium, nitrogen, xenon and helium.

[0024] Furthermore, in the above technical solution, the temperature of the sintering treatment in step (3) is 300-500° C., and the sintering time is 1-3 hours.

[0025] The third object of the present invention is to provide the application of the above-mentioned sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 in the positive electrode material of sodium ion battery.

[0026] The fourth object of the present invention is to provide a sodium ion battery positive electrode material, which includes a positive electrode active material, a conductive agent and a binder, and the positive electrode active material is the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 described above.

[0027] Furthermore, in the above technical scheme, the content of Na4Fe(PO4)2P2O7(NFPP) in the positive electrode material is 50-95% by mass percentage, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, as well as specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0028] Furthermore, in the above technical solution, the Fe content in the positive electrode material is 1-30% by mass percentage, for example, it can be 1%, 5%, 10%, 15%, 20%, 25% or 30%, as well as specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0029] Furthermore, in the above technical solution, the P content in the positive electrode material is 0-85% by mass percentage, for example, it can be 1%, 5%, 10%, 15%, 30%, 50% or 85%, as well as specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0030] Furthermore, in the above technical solution, the conductive agent in the positive electrode material is acetylene black or carbon black.

[0031] Furthermore, in the above technical solution, the content of the conductive agent in the positive electrode material is 1-20% by mass percentage, for example, it can be 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%, as well as specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention will no longer list them exhaustively.

[0032] A fifth object of the present invention is to provide a sodium ion battery positive electrode, which includes a current collector and a positive electrode material coated and / or filled on the current collector, and the positive electrode material is the sodium ion battery positive electrode material described above.

[0033] The sixth object of the present invention is to provide a sodium ion battery, which includes a pole core and a non-aqueous electrolyte, wherein the pole core and the non-aqueous electrolyte are sealed in a battery casing, the pole core includes a positive electrode, a negative electrode and a separator, and the positive electrode is the positive electrode of the sodium ion battery described above.

[0034] The present invention provides a Na4Fe(PO4)2P2O7 positive electrode active material and a preparation method and application thereof, wherein the material has good electrochemical properties. A sodium ion battery using Na4Fe(PO4)2P2O7 as a positive electrode active material has high specific capacity and stable cycle performance, and also shows good cycle stability under a high temperature environment of 60°C, meeting safety requirements. The advantage of Na4Fe(PO4)2P2O7 lies in its sodium ion-rich structure and transition metal and phosphorus co-doped lattice structure, which leads to higher specific capacity and stable cycle performance, and has broad application prospects.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention synthesized Na4Fe(PO4)2P2O7, a sodium-rich positive electrode active material. The battery using Na4Fe(PO4)2P2O7 as the positive electrode active material exhibited a high efficiency of 107 mAh g at 0.1C. -1 The initial capacity of the battery was 2.34 W and 1.32 W, and the battery showed stable cycling performance over 1000 cycles with a capacity retention of 82%. These materials have high specific capacity and stability due to their sodium-enriched structure.

[0037] (2) Under elevated temperature conditions (60 °C), the battery exhibits improved cycling stability, addressing the safety issue of preventing thermal runaway. DETAILED DESCRIPTION

[0038] The present invention relates to a method for preparing Na4Fe(PO4)2P2O7 positive electrode active material (NFPP), which adopts a hydrothermal reaction (heat treatment) step, and obtains a target product by mixing raw materials in a stoichiometric ratio under specific conditions. In the method of the present invention, citric acid is used as a multifunctional precursor, and has the functions of a chelating agent, a reducing agent and a carbon source during the synthesis process. The present invention provides a simple and effective method for preparing Na4Fe(PO4)2P2O7 positive electrode active material, which can be used in the field of sodium ion batteries and has good application prospects.

[0039] The present invention is further described in detail below through implementation cases.

[0040] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0041] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0042] Example 1

[0043] A sodium ion battery positive electrode active material of this embodiment has a chemical formula of Na4Fe(PO4)2P2O7 and is prepared by the following method, the steps are as follows:

[0044] (1) Dissolve ammonium dihydrogen phosphate (NH4H2PO4), iron (II) acetate tetrahydrate Fe(CH3COO)2.4H2O, sodium hydroxide (NaOH) and citric acid in an appropriate amount of deionized water in a ratio of 4.7:0.5:1.7:1:2 to form a reaction mixture. The reaction mixture is fully reacted at 80°C for 7 hours;

[0045] (2) The solution obtained in step (1) is poured into an autoclave, and heat treated at 180° C. for 40 hours under an argon atmosphere, and then cooled to room temperature. The obtained solution is then subjected to ultrasonic treatment to increase dispersibility. Finally, the water in the solution is evaporated by heating to obtain a powdery product. Sintering is performed at a temperature of 400° C. for 2 hours under an argon atmosphere to improve the density and stability of the product.

[0046] The obtained product was used as the positive electrode active material of sodium ion battery for electrochemical performance test. The pole piece ratio was composite material: acetylene black: PVDF = 80:10:10. The metal sodium sheet was used as the reference electrode. The electrolyte used a carbonate solution containing sodium perchlorate. The molar concentration of sodium perchlorate in the electrolyte was 1 mol / L. The diaphragm used a glass fiber diaphragm to prepare a CR2032 button battery; wherein: the composite material was the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 prepared above in this embodiment. The obtained battery had a first cycle discharge specific capacity of 107mAh / g and a capacity retention rate of 87% after 300 cycles in a voltage window of 2.5-4.0V and a current density of 0.1C. And it showed stable cycle performance within 1000 cycles, maintaining a capacity retention rate of 82%. These materials have high specific capacity and stability, which is due to their sodium-enriched structure.

[0047] Example 2

[0048] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the heat treatment temperature used in step (2) of this embodiment is 100°C.

[0049] Example 3

[0050] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Example 1, except that the heat treatment temperature used in step (2) of this embodiment is 500° C. and the heat treatment time is 5 hours.

[0051] Example 4

[0052] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Example 1, except that the heat treatment temperature used in step (2) of this embodiment is 300° C. and the heat treatment time is 20 hours.

[0053] Example 5

[0054] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the sodium source used in this embodiment is sodium carbonate.

[0055] Example 6

[0056] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the sodium source used in this embodiment is sodium oxalate.

[0057] Example 7

[0058] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the sodium source used in this embodiment is disodium hydrogen phosphate.

[0059] Example 8

[0060] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the sodium sources used in this embodiment are sodium tartrate and sodium alginate, and the molar ratio of the two is 1:1.

[0061] Example 9

[0062] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the sodium sources used in this embodiment are sodium lactate and sodium humate, and the molar ratio of the two is 1:1.

[0063] Example 10

[0064] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the phosphorus source used in this embodiment is white phosphorus.

[0065] Embodiment 11

[0066] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the phosphorus source used in this embodiment is phosphorous acid.

[0067] Example 12

[0068] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the phosphorus sources used in this embodiment are phosphorus trioxide and phosphorus pentoxide, and the molar ratio of the two is 1:1.

[0069] Example 13

[0070] The preparation method of a positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the phosphorus sources used in this embodiment are diammonium hydrogen phosphate and phosphoric acid, and the molar ratio of the two is 1:1.

[0071] Embodiment 14

[0072] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is substantially the same as that in Embodiment 1, except that the dispersant used in this embodiment is anhydrous ethanol.

[0073] Embodiment 15

[0074] The preparation method of the positive electrode active material for a sodium ion battery in this embodiment is basically the same as that in Embodiment 1, except that the dispersants used in this embodiment are anhydrous ethanol and deionized water, and the volume ratio of the two is 1:1.

[0075] Comparative Example 1

[0076] Compared with Example 1, except that NaOH is not added, other steps and conditions are exactly the same as those of Example 1.

[0077] The obtained material was used as the positive electrode material for sodium ion battery for electrochemical performance test. The mass ratio of the electrode piece was composite material: acetylene black: PVDF = 80:10:10, and metallic sodium was used as the reference electrode to prepare CR2032 button battery. In the 2.5-4.0V voltage window and 0.1C current density, the first cycle discharge capacity was 104mAh / g, and the capacity retention rate after 300 cycles was 82%.

[0078] Comparative Example 2

[0079] Compared with Example 1, except that no phosphorus source is added, other steps and conditions are exactly the same as those of Example 1.

[0080] Comparative Example 3

[0081] Compared with Example 1, except that no iron source is added, other steps and conditions are exactly the same as those of Example 1.

[0082] Comparative Example 4

[0083] Compared with Example 1, except that the phosphorus source and the iron source are not added at the same time, other steps and conditions are exactly the same as those of Example 1.

[0084] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode active material for a sodium ion battery, characterized in that: Its chemical formula is Na4Fe(PO4)2P2O7.

2. The method for preparing the positive electrode active material for a sodium ion battery according to claim 1, characterized in that: The method specifically comprises the following steps: (1) Reaction step: dissolving a sodium source, a phosphorus source, an iron source, citric acid or a citrate in a suitable amount of a dispersant in a stoichiometric ratio to form a reaction mixture; and then reacting the reaction mixture at 60-80° C. for 5-10 hours; (2) Post-treatment step: pour the solution obtained in step (1) into an autoclave, continue heat treatment at 100-500° C. in an inert atmosphere for 2-48 hours, and then cool to room temperature; then ultrasonically treat the obtained solution to increase dispersibility; finally, evaporate the water in the solution by heating to obtain a powdered product, namely the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7.

3. The method according to claim 2, characterized in that: The sodium source in step (1) is any one of sodium acetate, sodium hydroxide, sodium carbonate, sodium oxalate, sodium nitrite, disodium hydrogen phosphate, sodium bicarbonate, sodium citrate, anhydrous sodium sulfate, sodium stearate, sodium oleate, sodium tartrate, sodium alginate, sodium carboxymethyl cellulose, sodium lactate or sodium humate, or a combination of at least two thereof.

4. The method according to claim 2, characterized in that: The phosphorus source in step (1) is any one of white phosphorus, yellow phosphorus, black scale, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphine, phosphorus trioxide, phosphorus pentoxide, diammonium hydrogen phosphate, ammonium dihydrogen phosphate or phosphoric acid, or a combination of at least two thereof.

5. The method according to claim 2, characterized in that: The iron source in step (1) is at least one of ferrous sulfate, ferric sulfate, ferric nitrate and ferric acetate.

6. Use of the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 according to claim 1 or the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 prepared by the method according to any one of claims 2 to 5 in sodium ion battery positive electrode materials.

7. A positive electrode material for a sodium ion battery, comprising a positive electrode active material, a conductive agent and a binder, characterized in that: The positive electrode active material is the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 described in claim 1 or the sodium ion battery positive electrode active material Na4Fe(PO4)2P2O7 prepared by the method described in any one of claims 2-5.

8. The sodium ion battery positive electrode material according to claim 7, characterized in that: Calculated by mass percentage, the content of the positive electrode active material Na4Fe(PO4)2P2O7 in the positive electrode material is 50-95%.

9. A positive electrode for a sodium ion battery, comprising a current collector and a positive electrode material coated and / or filled on the current collector, characterized in that: The positive electrode material is the sodium ion battery positive electrode material according to claim 8.

10. A sodium ion battery, characterized in that: The battery comprises a pole core and a non-aqueous electrolyte, wherein the pole core and the non-aqueous electrolyte are sealed in a battery casing, the pole core comprises a positive electrode, a negative electrode and a separator, and the positive electrode is the positive electrode of the sodium ion battery according to claim 9.